(untitled) (World Bulletin of Social Sciences, 2025)
The article examines compound ethnographisms in the language of Kazakhs living in Karakalpakstan. The author argues that compound ethnographisms are formed through various linguistic processes such as combination, fusion, joining, and reduplication of words. Actively used nonfused ethnographisms in the local Kazakh language are classified into two main groups based on the patterns "noun + noun" and "noun + adjective," and their formation methods are analyzed.